Long-term outcomes of helical tomotherapy in lymph node-positive breast cancer following breast-conserving surgery - Zwicker, Felix; Raether, Luis-Philipp; Klepper, Rudolf; Hauswald, Henrik; Höfel, Sebastian; Huber, Peter E.; Debus, Jürgen; Schempp, Michael (Anticancer research, 2025)
Background/Aim: Adjuvant radiotherapy is an integral component of the interdisciplinary curative treatment of lymph node-positive breast cancer. We investigated long-term clinical outcomes of helical tomotherapy following breast-conserving surgery. - Patients and Methods: This single-center analysis included 80 female patients with breast cancer stages T1-T4 and lymph node metastasis (N1-N3) who underwent breast-conserving surgery, sentinel node biopsy, and/or axillary lymph node dissection. Patients received adjuvant fractionated radiation therapy to the whole breast and regional lymph node areas using helical tomotherapy. Boost irradiation was delivered sequentially or through the simultaneous integrated boost technique. Local control (LC), metastasis, survival, toxicity, and secondary malignancy rates were retrospectively analyzed. - Results: The mean follow-up duration was 75 months. The 5- and 8-year overall survival rates were 89.4% and 87.0%, respectively. LC rates at 5- and 8-year were 98.7%, and metastasis-free survival rates were 91.2% and 85.2%, respectively. Acute erythema occurred in 70% (Grades 1-2) and 26% (Grade 3) of patients. Ipsilateral arm lymphedema of Grade 1 and Grade 2 developed in 10% and 1.3% of the treated patients, respectively. Acute or late toxicities exceeding Grade 3 were not observed. - Conclusion: Helical tomotherapy showed excellent long-term results and low toxicity rates as adjuvant radiotherapy in patients with lymph node-positive breast cancer. The incidence of secondary malignancies was relatively low and corresponded to the preexisting records on radiation therapy. Broader clinical implementation of helical tomotherapy could benefit patients.